A Review on Wildlife Rescue Activities in North Kerala, India - Roshnath, R.; Jayaprasad, D. (Indian Forester, 2017)
Human-wildlife interactions are increasing progressively with decrease in natural habitat. Of which, many of the interactions are detrimental to wildlife which had resulted in formation of Rapid Response Teams (RRT) in each district under the Forest Department. This data explains the present situation of rescue activities in North Kerala. The RRT of each district were visited and data on rescues such as number of rescues, species of animal rescued, date of rescue etc were collected, complied and interpreted. We also discuss on the limitation and include recommendations for better rescue and rehabilitation activities in the area.